Identity Economics and the Creative Economy, Old and New - Herrmann-Pillath Carsten (Cultural Science)
I propose to associate the recent approaches to the economics of identity (Akerlof and Kranton, Davis) with the social network model of creative industries developed by Potts, Cunningham, Hartley and Ormerod. This implies that the latter just highlights a special case of the more general phenomenon that all economic activity is simultaneously involved in the process of agent identity formation. This conclusion is further supported by adding a third theoretical pillar, the theory of status goods. Status orders and agent identities appear to be major determinants of the nature of economic systems, resulting in contingent boundaries between systemic categorizations of production and consumption, or notions of productive processes versus non-productive ones. From that perspective, the major novelty in the emerging creative economy, viewed as a new kind of economic system, is the structural change of the social networks, which become less hierarchical and more integrated, resulting in the endogenization of identity formation. Changes in the agent identity trigger the further evolution of the economic system. This is mainly a move from an elitist and politically controlled system of the production of identities to a democratic and self-organized one, which is institutionally reflected in the increasing “marketization” of culture as a surface phenomenon. This relates to the ongoing debates over the redefinition of fundamental economic activities in the creative economy, such as viewing consumption as an essential part of the production of cultural goods.